What Is the Influence of the “Quality Manpower Training for Job Qualification Upgrades” Labor Policy and Its Implications on Employee’s Motivation, Engagement and Retention? - Yi-Chen, Wu (2011)
Owing to the global economic downturn, a lot of countries are suffering from the problem of ever increasing unemployment rate. Governments are implementing labor policies in order to better alleviate the problem of unemployment. Taiwan is no exception seriously affected by the global economic crisis. The unemployment rate had reached to the highest point in the year of 2008. Among the unemployed population, people aged from twenty and twenty-nine is the government’s one of the most and biggest concerns. To revitalize the economy and solve the unemployment problem, the Quality Manpower Training for Job Qualification Upgrades Policy is designed and carried out by Taiwan government to especially help the newly graduated students find jobs so as to overall decrease the unemployment rate. This pilot study is thus administered to investigate the problems and influence of this labor policy and to discuss the implications on employees’ motivation, satisfaction, and retention. Viewpoints from the both parties— employees and managers are presented through interviewing ten employees and two managers from different industries so as to have a more complete picture of the examination of the policy. Analysis of their viewpoints will be alongside provided. Suggestions to the policy in terms of salary administration and commitment fostering will also be presented and discussed.